The role of systems theory in political science: The case of unemployment in Spain - Parra-Luna, Francisco (Acta Europeana Systemica, 2020)
This paper will be consecrated to the problem of unemployment in Spain from the perspective of Systems Theory. But first I would like to emphasize, in a very schematic form, some of the possibilities and advantages of Systems Theory in Political Science. The purpose is only to suggest that the application of some theoretical and methodological principles of Systems Theory could contribute significantly to the development and efficiency of political systems. Let us say for the moment that the endevour requires to fulfill two main prerequisites: first to adopt the basic systemic principle which is to select the essential variablesfor any given piece of research within a polity; and second, to discover the ”system of values” that underlines this polity. To ignore these two fundamental prerequisites should be in principle theoretical and methodologically criticized as we hope to show when we study the unemployment problem in Spain. The application of the model could reduce unemployment from the current 17,1 % until some 12% in the period of 4 years.